Gen Z and Ageism: Public Policy Perspective - Fadia Karella Rismala; Ana Kumalasari; Heny Suhindarno; Adil Hassan Ibrahim (Journal of Law, Politic and Humanities, 2025)
The difficulty of finding a job due to the maximum age limit on job vacancies makes the unemployment rate in Bojonegoro Regency still relatively high. This research aims to identify whether the employment policies set by the government are appropriate and non-discriminatory. The research method used is qualitative. This type of research is descriptive research. The data collection process is carried out by means of interviews and observations. Informants or sources are residents of Bojonegoro Regency who meet the criteria, namely Generation Z and are currently experiencing difficulties in finding work due to age restrictions. The technique of determining informants uses probability sampling techniques, namely purposive sampling. This research uses primary data sources and secondary data sources. The theory used in this research is Iversen's theory, namely Ageism has three indicators, namely Prejudice, Stereotypes and Discrimination. This research uses a case study approach. The findings obtained in this study are that policies in local regulations on employment have not been effective in overcoming age discrimination in the workplace, resulting in reduced employment opportunities. This has a negative impact on Generation Z in Bojonegoro Regency. Thus, this research provides theoretical contributions for the Bojonegoro Regency Government to formulate more effective employment policies